Topical polyethylene glycol as a novel chemopreventive agent for oral cancer via targeting of epidermal growth factor response. - Ramesh K Wali; Dhananjay P Kunte; Mart De La Cruz; Ashish K Tiwari; Jeffrey Brasky; Christopher R Weber; Tina P Gibson; Amir Patel; Suzana D Savkovic; Bruce E Brockstein; Hemant K Roy (PLoS ONE, 2012)
Head and neck squamous cell carcinoma (HNSCC) is a major cause of morbidity and mortality underscoring the need for safe and effective chemopreventive strategies. Targeting epidermal growth factor receptor (EGFR) is attractive in that it is an early critical event in HNSCC pathogenesis. However, current agents lack efficacy or have unacceptable toxicity. Several groups have demonstrated that the over-the-counter medication, polyethylene glycol (PEG) has remarkable chemopreventive efficacy against colon carcinogenesis. Importantly, we reported that this effect is mediated through EGFR internalization/degradation. In the current study, we investigated the chemopreventive efficacy of this agent against HNSCC, using both the well validated animal model 4-NQO (4-nitroquinoline 1-oxide) rat model and cell culture with the human HNSCC cell line SCC-25. We demonstrated that daily topical application of 10% PEG-8000 in the oral cavity (tongue and cavity wall) post 4NQO initiation resulted in a significant reduction in tumor burden (both, tumor size and tumors/tumor bearing rat) without any evidence of toxicity. Immunohistochemical studies depicted decreased proliferation (number of Ki67-positive cells) and reduced expression of EGFR and its downstream effectors cyclin D1 in the tongue mucosa of 4NQO-rats treated with PEG. We showed that EGFR was also markedly downregulated in SCC-25 cells by PEG-8000 with a concomitant induction of G1-S phase cell-cycle arrest, which was potentially mediated through upregulated p21(cip1/waf1). In conclusion, we demonstrate, for the first time, that PEG has promising efficacy and safety as a chemopreventive efficacy against oral carcinogenesis.